Peran Generasi Muda Sebagai Agent Of Change Guna Membangun Kearifan Budaya Lokal Dalam Ajaran Tri Hita Karana - Putu Sanjaya (Jurnal Penelitian Agama Hindu, 2022)
Bali is one of the islands in Indonesia which is a tourist destination for both domestic and foreign tourists. The uniqueness and wisdom of local culture and social life of the community is the main attraction for tourists who come to Bali. In the era of the globalization era where Hindu religious traditions and culture in Bali began to fade due to foreign cultures being able to dominate people's mindsets, that way people tend to be influenced by foreign cultures, such as imitation in determining one's direction in behavior to imitate others. Who became his idol. In changing human behavior, it is necessary to cultivate the three basic frameworks of Hinduism through the basic concept called Tri hita karana found in the holy book Bhagawad Gita (III 10). Therefore, the role of the younger generation as Agents of Change, in order to build local cultural wisdom is urgently needed in creating change to preserve and maintain culture in Bali. The purposes of this article are (1) to describe the role of the younger generation as agents of change in developing local cultural wisdom (2) to describe the government's contribution in anticipating foreign cultures entering Bali (3) to describe the role of the younger generation as agents of change in preserving local cultural wisdom The method used in this article is the Qualitative Method and the collection of literature review data includes journals, reports and population numbers. The results of the article are (1) Growing the younger generation in developing and maintaining local cultural wisdom (2) Preserving local cultural wisdom through the teachings of Tri hita karana (3) Being able to build community character education in the teachings of Tri hita karana.